Development of E-Assessment to Measure Critical Thinking in Chemistry Learning - Coryna Oktaviani; Mauliza Mauliza; Nurhafidhah Nurhafidhah (EduChemia: Jurnal Kimia dan Pendidikan, 2026)
The quality of learning is directly related to quality of assessment. In education, assessment is also referred to as evaluation. The purpose of this study is to develop a practical e-assessment to evaluate critical thinking skills that can be applied efficiently to meet the needs of teachers and students in the field of chemistry education. This study uses a research and development (R&D) approach, utilizing a 4-D development framework (Define, Design, Develop, and Disseminate). The instruments used include a needs analysis questionnaire, construct validity test, and practicality test. Data analysis used Aiken's V formula and percentages. The Aiken's V values obtained in the validation of the electronic assessment product for stoichiometry material were 0.85 and 0.83 for the electronic assessment of redox reaction material, with both criteria showing valid. In addition, the feasibility test conducted on chemistry teachers in five Langsa State Senior High Schools showed an average e-assessment score of 85% for stoichiometry material and 86% for redox reactions, with both criteria being very practical. The results of implementing the e-assessment product to measure the critical thinking of students at Langsa State Senior High School obtained 67% with moderate criteria for testing stoichiometry material and 64% with moderate criteria for testing redox reaction material.